2012
DOI: 10.1007/s00267-012-9899-1
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Changes in Kunzea ericoides var. microflora and Other Hydrothermal Vegetation at the Wairakei–Tauhara Geothermal Field, New Zealand

Abstract: Hydrothermal ecosystems are of high conservation and scientific value, but they are sensitive to external perturbations that result from development. This study examines the composition of vegetation at four plots at the Wairakei-Tauhara geothermal field, New Zealand, using the Scott height-frequency method, ground temperatures at 0.1- and 1-m depth, soil pH, and photographic surveys. It highlights the response of plant communities, in particular that of Kunzea ericoides var. microflora, in terms of compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Our analyses showed that soil temperature is the dominating effect on vegetation regeneration and root growth. Previous studies have also suggested that in geothermal fields, vegetation establishment and growth is strongly controlled by thermal gradients; ( Burns, 1997 ; Elmarsdottir et al, 2003 ; Muukkonen, 2006 ; Chiarucci et al, 2008 ; van Manen and Reeves, 2012 ), having fundamental effects on the abiotic and biotic processes determining the distribution and density of geothermal vegetation ( Chapin, 1983 ; Saito et al, 2009 ; Aalto et al, 2013 ; Olefeldt et al, 2013 ). Apart from growth rates and community composition, soil temperature may also affect species-specific growth forms as is the case with the dominant woody species in our study system ( Harris, 1996 ; Boothroyd, 2009 ; Beadel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses showed that soil temperature is the dominating effect on vegetation regeneration and root growth. Previous studies have also suggested that in geothermal fields, vegetation establishment and growth is strongly controlled by thermal gradients; ( Burns, 1997 ; Elmarsdottir et al, 2003 ; Muukkonen, 2006 ; Chiarucci et al, 2008 ; van Manen and Reeves, 2012 ), having fundamental effects on the abiotic and biotic processes determining the distribution and density of geothermal vegetation ( Chapin, 1983 ; Saito et al, 2009 ; Aalto et al, 2013 ; Olefeldt et al, 2013 ). Apart from growth rates and community composition, soil temperature may also affect species-specific growth forms as is the case with the dominant woody species in our study system ( Harris, 1996 ; Boothroyd, 2009 ; Beadel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the TOC content resulted from both a small amount of litter—the projective cover of vegetation decreases from the periphery to the center of the hydrotherm—and sulfuric acid decomposition of organic matter. These processes were typical for endothermal soils affected by the steam-heated acid-sulfate waters in Kamchatka 18 , New Zealand 9 , 59 – 62 , Iceland 22 , California 37 , Japan (Hokkaido 63 and the Kusatsu-Shirane volcano region 64 ).…”
Section: Resultsmentioning
confidence: 93%
“…In the South Sandwich Islands (maritime Antarctic), bryoflora richness was maximal at the thermal ecosystems where the topsoil surface temperature reached 47 °C 74 , 75 . In the forest landscapes of Kamchatka 76 , Hokkaido 48 , 77 , California 37 and New Zealand 7 , 9 , 61 , 62 , 78 , the inflow of heated thermal waters resulted in disappearance of woody plants. Vegetation was sparse at the endothermal soils with surface temperatures of more than 50 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Makeup water is approximated by Clark et al [77] and calculated per unit energy generated based on production values given by Kaya [24]. In several cases, endemic organisms are reported [89,90]. Thus, even if geothermal power generation plays only a minor role for electricity generation worldwide, local effects on biodiversity may be substantial.…”
Section: Impact On Biodiversitymentioning
confidence: 99%